Empowerment Evaluation of Programs Involving Youth - Sarah Heath; Katherine Moreau (Journal of MultiDisciplinary Evaluation)
Background: Participatory and collaborative evaluation approaches, including Empowerment Evaluation (EE), are useful for evaluating programs involving youth. Empowerment evaluation involves stakeholders in the evaluation process through a set of structured steps. It is primarily concerned with empowering, illuminating, and building program beneficiaries’ self-determination. Given the emphasis that EE places on inclusivity of stakeholders, it appears to be a good fit for evaluating programs that involve youth.